Comparing the Effect of Group and Individual Mindfulness‐Based Cognitive Behavior Therapy on Happiness of Postmenopausal Women: A Randomized Controlled Trial in Iran - Basad Terikani; Parvin Abedi; Maryam Gholamzadeh Jofreh; Maryam Dastoorpour; Poorandokht Afshari (Health Science Reports)
ABSTRACT Background and Aims Happiness is an important factor for decreased quality of life in some postmenopausal women. This study aimed to compare the effects of group and individual mindfulness‐based cognitive behavioral therapy (MBCT) on the happiness of postmenopausal women. Methods This was a randomized controlled trial of 48 postmenopausal women who received group or individual MBCT counseling. Literate postmenopausal women aged 50–64 years, 1–10 years after menopause, and with Happiness Scale scores less than 40–42 were recruited for this study. A demographic questionnaire and the Oxford Happiness Questionnaire were used to collect the data. Women in the group counseling group received 8 sessions of counseling according to MBCT, while women in the individual counseling group received counseling individually. Independent t‐tests, Chi‐square tests and two‐way Repeated Measures ANOVA were used to analyze the data. Results The scores of all components of happiness including self‐concept, life satisfaction, mental preparation, active well‐being, aesthetic sense, self‐efficacy, and hope, increased in both groups immediately after and 1 month after the completion of the intervention. The total happiness score in the group counseling group improved from 33.39 ± 5.57 before the intervention to 48.91 ± 6.77 and 48 ± 6.38 after the intervention and during the follow‐up period, respectively (p value < 0.001). These scores in the individual counseling group improved from 32.13 ± 5.40 to 46.04 ± 7.80 and 45.13 ± 7.26 immediately after the intervention during the follow‐up period, respectively (p value < 0.001). There was no significant difference between the two groups. Conclusion Our results showed that although the scores of all components of happiness were slightly greater in the counseling group than the individual group, there was no significant difference between the two groups. Using either method is recommended for increasing the happiness of postmenopausal women.